Smoking patterns and willingness to quit: A cross-sectional study in Al Ain City, UAE - Moawia M Al-Tabakha; Muaed J Alomar; Mariam N G Awad; Khairi M S Fahelelbom (Wolters Kluwer Medknow Publications, 2019)
Background: Tobacco use is the major cause of preventable morbidity and mortality. The main objectives of this study were to identify smokers willing to participate in quit smoking campaigns using social media and to identify smoking habits of everyday smokers in Al Ain City, United Arab Emirates (UAE). Research Design and Methods: Everyday smokers from Al Ain city of the UAE were surveyed in different locations of the city including malls and specialized tobacco-selling shops. They were interviewed using a semi-structured survey and the information was recorded by one assessor. The information gathered included type and frequency of tobacco use, smoking history and habits, quitting history, desire to quit, and the preferred communication platform. Result: A total of 412 regular adult smokers were interviewed in which the majority (95%) reported first smoking at or before the age of 28 years. Participants were mainly UAE nationals (33.7%), Egyptians (14.1%), Syrians (12.9%), and Jordanians (10.9%). Manufactured cigarettes were the main form of tobacco consumption (59.5%), and smoking was mainly solitary (56.3%) and at home (26.3%) and coffee shops (24.9%). The majority of interviewed subjects (76.7%; 95% confidence interval [CI]: 72.4%-80.5%) expressed their interest to quit smoking in the future and 55.3% (95% CI: 50.5%-60.2%) were ready to get involved immediately in a smoking cessation program. Of those, 80.3% (95% CI: 74.6%-84.9%) preferred WhatsApp for receiving smoking cessation motivational education. Conclusion: The majority of smokers started at younger ages, which warrant the age of smoking restriction to be raised to 29 years instead of 18 years by the health authority. Everyday smokers were aware of the potentially hazardous effects of tobacco smoking and many were willing to accept help to quit smoking that involves the use of WhatsApp.